2019
DOI: 10.1111/cas.14155
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profile of urine has high diagnostic sensitivity compared to cytology in non‐invasive urothelial bladder cancer

Abstract: Cytology is widely conducted for diagnosis of urothelial bladder cancer; however, its sensitivity is still low. Recent studies show that liquid biopsies can reflect tumor genomic profiles. We aim to investigate whether plasma or urine is more suitable for detecting tumor‐derived DNA in patients with early‐stage urothelial bladder cancer. Targeted sequencing of 71 genes was carried out using a total of 150 samples including primary tumor, urine supernatant, urine precipitation, plasma and buffy coat from 25 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…Recent studies have shown that the concentration of cfDNA in urine is even higher than that in blood. For example, Yosuke et al conducted gene detection tests on urine supernatants, urine precipitate, and blood samples from patients with BC, cystitis, and benign tumors 21 . Half of the somatic mutations present in tumors were detected in urine samples (53% in urine supernatant and 48% in urine precipitate), while 2% were detected in the blood plasma.…”
Section: Components Of Urine Biopsymentioning
confidence: 99%
“…Recent studies have shown that the concentration of cfDNA in urine is even higher than that in blood. For example, Yosuke et al conducted gene detection tests on urine supernatants, urine precipitate, and blood samples from patients with BC, cystitis, and benign tumors 21 . Half of the somatic mutations present in tumors were detected in urine samples (53% in urine supernatant and 48% in urine precipitate), while 2% were detected in the blood plasma.…”
Section: Components Of Urine Biopsymentioning
confidence: 99%
“…Besides ctDNA, urothelial tumors have close contact with urine, thus, urinary biomarkers are highly promising as noninvasive tools. Somatic mutations are reliably detected in urinary cell-pellet DNA and cfDNA [75][76][77][78][79][80], and the level of cfDNA in urine supernatants was associated with pathologic features and disease progression, which makes urine tumor DNA have great potential in clinical detection, especially in the early stages of BC [81,82,80,79,83,84]. Current research on the clinical significance of UcfDNA detection for BC is increasing ( Table 2).…”
Section: Ta B L Ementioning
confidence: 99%
“…Increased levels of FGFR3 and Phosphatidylinositol-4,5bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) mutated DNA in urine and plasma are indicative of later progression and metastasis in BC. Hirotsu et al [81] compared detection rates of 71 UC commonly mutated genes in urine supernatants, urine precipitation, and plasma from 25 BC patients and 5 patients with cystitis and benign tumor. The diagnostic sensitivity of the genetic analysis was higher in urine DNA (67%-78%) compared to cfDNA or conventional cytology (22%) in NMIBC.…”
Section: Ta B L Ementioning
confidence: 99%
“…We searched TCGA data and literature (5,(16)(17)(18)(19)(20)(21)(22) and selected 71 genes related to urological cancer (kidney cancer, prostate cancer, and BC) as described previously (23). A total of 3,652 primer pairs were designed by Ion AmpliSeq Designer contained within this panel (covering 365.34 kb) (23). Library preparation was conducted by amplicon-based multiplex PCR with Ion AmpliSeq Plus Kit (Thermo Fisher Scientific) as described previously (24)(25)(26).…”
Section: Gene Selection and Targeted Sequencingmentioning
confidence: 99%